Islamic Feminism in Iran: Feminism in a New Islamic Context - Ahmadi, Fereshteh (Journal of feminist studies in religion, 2006)
, Ahmadi reveals in this article how, by emphasizing the historical context of the holy texts, challenging the clergy's monolithic interpretational power, and reformulating Islamic concepts and law from a "feminist" perspective, Islamic feminists in Iran are rethinking gender in Islam. Not only are Islamic feminists opening the doors of interpretation of sacred texts and debates on women's issues to groups other than Muslims but they have also broken with the reactive gender conservatism and West phobia prevailing among fundamentalists, connected themselves with Western feminism, and woven new connections between Muslim women and Western feminism.